Microwave Photonic Up- and Down-Converter with Tunable Phase Shift Based on an Integrated Dual-Polarization Dual-Parallel Mach–Zehnder Modulator without Optically Filtering. Issue 2 (3rd March 2020) - Chen, Dou; Ma, Jianxin
ABSTRACT: In this paper, we propose and numerically simulate a microwave photonic phase-tunable frequency converter (MPPTFC) without optically filtering to realize both frequency up- and down-conversion and a full 360° phase-shift for the microwave signal based on an integrated dual-polarization dual-parallel Mach–Zehnder modulator (DP-DPMZM). In the proposed scheme, both microwave RF signal and frequency-tunable local oscillator (LO) are modulated on the lightwave by single-sideband carrier suppression (SSB-CS) modulation to generate optical orthogonally polarized optical tones carrying RF signal with up- or down-converted frequency. A PolM that can support lightwave modulation with opposite modulation indices in transverse electric (TE) and transverse magnetic (TM) modes is used to introduce a phase difference between the two modes. Then the orthogonally polarized optical tones are aligned into a single polarized state by a polarizer (Pol) and detected by a photodiode (PD), a frequency-converted and phase-shifted microwave signal can be obtained. Simulation results demonstrate that the proposed MPPTFC can up-/down-convert the microwave signal with a tunable frequency shift of LO frequency and realize a 360° continuously tunable phase shift via the DC bias voltage of the PolM simultaneously.